Field notes contributed by Paul Martsching, summer 1986 - Martsching, Paulet al (1986)
List of birds and locations contributed by Paul Martsching with observer Steve Lekwa. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of summer 1986. Epson - sheet feed/flatbed